Pendidikan Islam Dalam Geraan Transnasional - Desyi Rosita; Aat Royhatudin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
In this paper, it will be analyzed descriptively that transnational Islamic movements in religious education have strong strategies and doctrines, systematic and systematic curriculum design, hidden curriculum, especially in learning activities in simple places, ranging from mosques, pesantren and even madrasa, and tertiary institutions as high institutions by including values ​​and religious teachings as Islamic Puritanism Movement which is very urgent to return to the teachings of the Quran and Sunnah, the teachings of pure Islam and to leave even eradicate other teachings outside the teachings of the Quran and Sunnah. But in this paper there is an alternative offer of a deconstruction that explains that the education of Rosulullah with ta'dibiyah has a great character, which reflects a pious personality so that the message of grace leads to peace and plurality and tolerance in religion.